Peran Orang Tua Siswa Kelas IV SD Negeri Sumuranja 2 dalam Membantu Belajar di Rumah - Febri Yanto; Ima Ni’mah Chudari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This study illustrates the role of parents of grade IV students of SD Negeri Sumuranja 2 inhelping children learn at home. Parental responsibility is the most important, in terms ofattention and affection for children, so that children feel comfortable and helped while studying at home. Parental guidance is carried out when the child has not yet taken formal education, namely school, the role of parents is an important thing to do as a substitute for teachers to help children learn at home. As parents, they cannot fully release it to the school, because at home the child has quite a lot of time so that the role of parents is needed in helping children learn. This study was conducted because the author wanted to know the perspective of parents when helping children learn at home, besides that they can know the efforts and ways that parents of students make in helping learn at home. The research method used is descriptive qualitative, used to describe a situation or events according to reality. In this study, researchers collected data using questionnaire instruments, interviews, and documentation studies. The results showed that the perspective of parents in helping and guiding children is quite good, with good communication, supervising at the time of learning, providing facilities, guiding, helping the learning process, providing knowledge, and applying a disciplined attitude. The difficulties and obstacles experienced when helping children learn at home are the limited knowledge of parents in learning materials. So the efforts made are to help by looking for answers through textbooks or searching the internet. The role of parents is important, because in addition to helping in theory, it also strengthens the sense of family so that it can be harmonious and by motivating children to be more enthusiastic in learning.